The Role of Value Congruence and Service Trust to Increase Fintech Use Among Women: English - Junianto, Yopy; Wirawan, Wirawan (Review of Management and Entrepreneurship, 2026)
Economic growth is very dependent on the level of understanding of financial literacy and the technological level of the people in it. People with high financial and technological literacy will increasingly have regular and positive patterns in using fintech. The greater the use of fintech for everyday life, the more the economy will improve. This research aims to investigate the influence of service trust on fintech use through value congruence and Value in use as mediator variables. The authors used women as a sample because women make more purchasing decisions than men. With a sample size of 163 people, the author used primary data with SEM as the analysis method. The results of this study show that women with a high level of trust will be increasingly encouraged to use fintech. Meanwhile, Value in use weakens the relationship between service trust and fintech use, but value congruence is a partial mediator between service trust and fintech use. In this research, the level of trust is essential in increasing the use of fintech, which is the main factor in improving the economy's future.